Cyclic shear behavior and strength capacity of prestressed concrete walls in high-rise buildings. (1st September 2022) - Cheng, Xiaowei; Ji, Xiaodong; Xu, Ziguo; Wan, Yixiu; Wang, Tao
Highlights: PC walls are used to enhance seismic performance of tensile walls of tall buildings. Tests were conducted on PC walls under coupled axial forces and cyclic shear loading. Variable axial tension–compression forces decreased shear strength of PC walls. Design formulas of shear strength of PC walls are estimated. The truss idealization method for calculating shear stiffness of PC walls is validated. Abstract: To prevent adverse impact of axial tensile force on seismic performance of reinforced concrete (RC) walls, bonded prestressed concrete (PC) walls are proposed to use in high-rise buildings. These prestressed strands provide an initial axial compressive load on the walls to balance axial tensile forces induced by strong ground motions. Three low-aspect-ratio PC wall specimens were tested for various loading patterns, including constant axial forces or variable axial forces, combined with cyclic shear loading. The failure modes of wall specimens varied with loading patterns. The variation in axial forces decreased the normalized tensile-shear strength and compressive-shear strength by 20.0% and 11.2%, respectively. The wall specimen undergoing diagonal compression failure had a small ultimate drift ratio of 0.6%, while other two specimens had an ultimate drift ratio no less than 1.2%. The PC wall under axial tensile forces had significantly higher lateral strength and stiffness than a RC wall counterpart, because the prestressed force controlled the development of cracks and prevented the sliding failure. Both the JGJ 3–2010 (China) code formula and ACI 318–19 (U.S.) code formula significantly underestimate the shear strength of PC wall specimens. The ASCE/SEI 43–05 (U.S.) code formula appears to reasonably reflect the resisting mechanisms of PC walls and provides an accurate estimate to the shear strength of wall specimens. The truss idealization method provides a reasonable estimate for the cracked shear stiffness of PC walls under coupled axial tension-shear loading, while underestimates the cracked shear stiffness of PC walls under coupled axial compression-shear loading.